Development and Optimization of Solid Self Nanoemulsifying Drug Delivery (S-SNEDDS) Using D-Optimal Design for Improvement of Oral Bioavailability of Amiodarone Hydrochloride - Patel, Archita; Shelat, Pragna; Lalwani, Anita (Current Drug Delivery, 2015)
The solid-self nanoemulsifying drug delivery system (S-SNEDDS) of Amiodarone hydrochloride (AH) was prepared and evaluated. AH exhibits poor aqueous solubility (0.3-0.5 mg/ml) and therefore variable oral bioavailability. Capmul MCM, Cremophor RH-40 and Propylene glycol were identified as oil, surfactant and co-surfactant for preparing L-SNEDDS. D-optimal design was used to optimize the amount of components in liquid self nanoemulsifying drug delivery system (L-SNEDDS). Optimized AH-L-SNEDDS having 15.8 nm globule size and 99.5 %transmittance was then adsorbed on Neusilin US2 to form solid self nanoemulsifying drug delivery system (AH-SSNEDDS). AH loaded L-SNEDDS and S-SNEDDS were characterized for various physicochemical properties and solid state properties. In vitro dissolution, ex vivo drug release study and In vivo study were performed for pure AH, AH-LSNEDDS and AH-S-SNEDDS. Both AH loaded L-SNEDDS and S-SNEDDS showed more than 95% drug release in 20 min during drug release studies. In vivo study revealed that release of AH from S-SNEDDS was 2.26 times and LSNEDDS was 1.83 times higher than that from suspension when given to rabbits (p < 0.01). The optimized S-SNEDDS was found to be stable and its shelf life was found to be 2.2 years. S-SNEDDS could serve as a potential drug delivery system for AH.
Keywords: Amiodarone hydrochloride